The Development of Sustainable Profession (PKB) of Teachers in Senior High School - Tibyan Ravaie; Aswandi Aswandi; M. Chiar (JETL (Journal of Education, Teaching and Learning), 2018)
This research is to know 1) Effort done by teacher of State Senior High School 1 Pemangkat (SMA Negeri 1 Pemangkat) Sambas Regency for Self Development; 2) Business undertaken by teacher of SMA Negeri 1 Pemangkat Sambas District for Scientific Publication; 3) Business has undertaken by teacher of SMA Negeri 1 Pemangkat Sambas District to Produce Innovative Works; 4) Knowing the effort to overcome the factors that become teachers of SMA Negeri 1 Pemangkat Sambas District in their Sustainable Development of Professions. This type of research includes descriptive research with qualitative approach. The result of interview and literature study is analyzed so that it can answer the research question. based on the research undertaken the results obtained as follows 1) Enterprises undertaken by teachers SMA Negeri 1 Pemangkat for their sustainable profession development through MGMP activities subject teachers routinely conducted every 1 month; 2) Most teachers of SMA Negeri 1 Pemangkat have not shown their maximum efforts in developing their profession, especially in making scientific publications / scientific papers and innovative works; 3) Teachers of SMA Negeri 1 Pemangkat who try to do activities related to their professional development are driven by internal factors (self desire) and external factors that is moral support from the principal; 4) Most teachers of SMA Negeri 1 Pemangkat experience difficulties in developing their sustainable profession.